Dampak Pajak Pertambahan Nilai (PPN) terhadap Daya Beli Masyarakat Medan di Pasar Tradisional MMTC Medan - Ria Agustina Sigiro; Tri Febriani Sipayung; Hesti Herawati Siagian; Trivena Kezia Br Silaban; Stevani Nababan; Emia Perangin Angin (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This research aims to analyze how the increase in Value Added Tax (VAT) rates operates after the Harmonization of Tax Regulations Law (HPP Law) is enacted, specifically regarding the microeconomic ecosystem, particularly in the MMTC Medan Market. Although VAT plays an important role in strengthening state finances, there are concerns about its regressive nature and its impact on the purchasing power of low-income citizens and the sustainability of Micro, Small, and Medium Enterprises . This research uses a qualitative approach with case study methods and semi-structured in-depth interviews with consumers (students and local residents) and MSME actors (grocery store owners) at MMTC Medan Market. This research focuses on how economic actors at the grassroots level respond to policy changes. The research results indicate that the increase in VAT rates serves as a trigger and intensifier of the decline in public purchasing power. Consumers are responding with defensive strategies such as limiting the frequency and amount of shopping, switching to cheaper goods, and as evidenced by the decline in merchant turnover. On the other hand, MSME actors are taking survival steps by absorbing the impact, which means holding back some of the price increases by reducing profit margins, dividing products into smaller sizes, and strengthening relationships with customers. However, this strategy poses a risk to long-term business sustainability. Additionally, there are deep differences in understanding, where the policy is considered unfair because the